2017
DOI: 10.1061/(asce)gt.1943-5606.0001740
|View full text |Cite
|
Sign up to set email alerts
|

Single-Grain Virtualization for Contact Behavior Analysis on Sand

Abstract: This is the accepted version of the paper.This version of the publication may differ from the final published version. outline of the grain is required. The volumetric object is obtained by reconstructing the planar projections of the grain acquired at different angles of rotation using a standard camera. Depending on the lenses system, the resolution of the images can be as good as of a few microns. A numerical representation of the real grain can be obtained by meshing the 3D image. The influence of grain mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…This aspect is significant for modelling grain-to-grain contact interaction in an assembly. In fact, contact response has a strong dependency on the grain shape as demonstrated in Nadimi & Fonseca (2017) for a series of tests on both silica and carbonate grains. Michalowski, et al (2017) also showed through single grain experiments that contact response for natural grains does not follow a Hertzian response due to the effect of shape.…”
Section: Introductionmentioning
confidence: 92%
“…This aspect is significant for modelling grain-to-grain contact interaction in an assembly. In fact, contact response has a strong dependency on the grain shape as demonstrated in Nadimi & Fonseca (2017) for a series of tests on both silica and carbonate grains. Michalowski, et al (2017) also showed through single grain experiments that contact response for natural grains does not follow a Hertzian response due to the effect of shape.…”
Section: Introductionmentioning
confidence: 92%
“…The stress distribution and fracture behaviour of the Brazilian disc under different arc loading angles have been investigated experimentally and numerically [39]. The results indicated that the Brazilian test with curved loading caused the stress concentration to be lower at the loading ends, but cannot promise that cracks initiate from the disc centre due to the ununiformed stress distribution at curved contact [25].…”
Section: Introductionmentioning
confidence: 99%
“…The Hertz-Mindlin model, which is used in many DEM studies, assumes that the contacting particles are smooth. While this model can capture key elements of contact mechanics, it is now clear that surface roughness has a measurable influence on the force-displacement relationship, particularly for normal loading and small deformation levels [2][3][4][5]. Several studies have emphasised the importance of roughness on the macroscopic soil stiffness (e.g.…”
Section: Introductionmentioning
confidence: 99%